2020
DOI: 10.3390/molecules25102451
|View full text |Cite
|
Sign up to set email alerts
|

Peculiar Structural Effects in Pure and Doped Functional Single Crystals of Complex Compositions

Abstract: Results of a detailed structural characterization of nominally pure and doped single crystals of scheelite, eulytin, and perovskite families obtained by melt methods were considered and analyzed. The influence of growth and post-growth annealing conditions on actual compositions of crystals is shown. The reasons for the coloration of the crystals are explained. A change in crystal symmetry due to crystal–chemical and growth reasons is considered. The use of structural analysis and X-ray absorption spectroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 169 publications
0
2
0
Order By: Relevance
“…32 It is known that the method of dopant introduction affects the actual composition and features of defect formation in crystals and hence their functional properties. 33,34 The aim of this work is to determine statistical and local structures, in particular, types and concentrations of point defects as well as crystallographic positions, local environments, and formal charges of dopant ions in Czochralski-grown Ca 3 (VO 4 ) 2 single crystals doped with manganese and cobalt introduced by the diffusion from Mn 2 O 3 and Co 3 O 4 solid phases. Structural features are comprehensively studied by single-crystal and powder synchrotron X-ray diffraction and conventional single-crystal X-ray diffraction as well as by X-ray absorption spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…32 It is known that the method of dopant introduction affects the actual composition and features of defect formation in crystals and hence their functional properties. 33,34 The aim of this work is to determine statistical and local structures, in particular, types and concentrations of point defects as well as crystallographic positions, local environments, and formal charges of dopant ions in Czochralski-grown Ca 3 (VO 4 ) 2 single crystals doped with manganese and cobalt introduced by the diffusion from Mn 2 O 3 and Co 3 O 4 solid phases. Structural features are comprehensively studied by single-crystal and powder synchrotron X-ray diffraction and conventional single-crystal X-ray diffraction as well as by X-ray absorption spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to irradiation leads to the appearance of photoinduced phenomena, such as photochromic and photodielectric effects [1]. X-ray diffraction, luminescence, and EPR studies have shown that the crystal lattice of such crystals contains point and extended defects, various clusters, including photoinduced ones, based on anionic MoO 4 groups that have captured photoelectrons [2,3]. In fact, PbMoO 4 single crystal is a partially disordered medium.…”
Section: Introductionmentioning
confidence: 99%